Second School of Engineering Research Symposium Book of Abstracts - (:unkn) unknown (School of Engineering, 2024)
Welcome to the Second PhD Research Symposium of the School of Engineering, a celebration of innovation, exploration, and the pursuit of knowledge in the field of engineering. We are delighted to present this book of abstracts, a compendium of the remarkable research undertaken by our talented PG researchers in the School. Within these pages, you will find a snapshot of the diverse and cutting-edge research that defines our School of Engineering. Our researchers have dedicated countless hours to complex problems, developing novel solutions, and pushing the boundaries of what is possible in the world of engineering. Each abstract is representative of the passion, dedication, and expertise of our PhD researchers. Their work not only contributes to the academic excellence of our School but also holds the promise of transforming industries, improving lives, and making a positive impact on society for a sustainable future. We thank the researchers who have shared their work in these pages, to their mentors, advisors and supervisors who have guided them on this intellectual journey, and to the faculty and staff who support and facilitate their research. As you explore this book of abstracts, we encourage you to engage with the research, to foster dialogue, and to seek opportunities for collaboration and innovation. Together, we can address the challenges of today and shape a more sustainable tomorrow.
School of Engineering Research Symposium (SERS)
PUBLISHED
Trinity College Dublin
Keywords: Nanoscience & Materials; Neuroscience; Next Generation Medical Devices; Smart & Sustainable Planet; Telecommunications; Bioengineering; Biomechanics, Biomedical Engineering; ELECTRONICS; Engineering Design; Environmental engineering; Fluid Dynamics; Medical Devices; Structural Design; Tissue Engineering; Transport; Wireless systems, Radio technology; Brain Injury; Stroke; Community; Environment and housing; Health